The Absence of the Transient Receptor Potential Vanilloid 1 Directly Impacts on the Expression and Localization of the Endocannabinoid System in the Mouse Hippocampus - Egaña-Huguet, Jon; Bonilla-Del Río, Itziar; Gómez-Urquijo, Sonia M.; Mimenza, Amaia; Saumell-Esnaola, Miquel; Borrega-Roman, Leire; García del Caño, Gontzal; Sallés, Joan; Puente, Nagore; Gerrikagoitia, Inmaculada; Elezgarai, Izaskun; Grandes, Pedro (Frontiers in Neuroanatomy, 2021)
The transient receptor potential vanilloid 1 (TRPV1) is a non-selective ligand-gated cationic channel involved in synaptic transmission, plasticity and brain pathology. In the hippocampal dentate gyrus, TRPV1 localizes to dendritic spines and dendrites postsynaptic to excitatory synapses in the molecular layer (ML). At these same synapses, the cannabinoid CB1 receptor (CB1R) activated by exogenous and endogenous cannabinoids localizes to the presynaptic terminals. Hence, as both receptors are activated by endogenous anandamide, co-localize and mediate long-term depression of the excitatory synaptic transmission at the medial perforant path (MPP) excitatory synapses though by different mechanisms, it is likely that they might be having an effect on each other from their opposite synaptic sites. In this study, we tested whether the absence of TRPV1 affects the endocannabinoid system. The results obtained using biochemical techniques and immunoelectron microscopy in a mouse model with the genetic deletion of TRPV1 show that the expression and localization of components of the endocannabinoid system, included CB1R, change upon the constitutive absence of TRPV1. Thus, the expression of fatty acid amide hydrolase (FAAH) and monoacylglycerol lipase (MAGL) drastically increased in TRPV1-/- whole homogenates. Furthermore, CB1R and MAGL decreased and the cannabinoid receptor interacting protein 1a (CRIP1a) increased in TRPV1-/- synaptosomes. In TRPV1-/- dentate ML, the excitatory terminals were less numerous and enlarged but the percentage of CB1R positive excitatory terminals was augmented. In the inner 1/3 ML, the proportion of CB1R particles significantly dropped in inhibitory terminals but raised significantly in excitatory terminals, neuronal mitochondria and dendrites. Particle distribution in inhibitory and excitatory terminals, mitochondria and astrocytes was not altered significantly in the outer 2/3 ML of TRPV1-/-. Altogether, these observations indicate the existence of compensatory changes in the endocannabinoid system upon TRPV1 removal, and endorse the importance of the potential functional adaptations derived from the lack of TRPV1 in the mouse brain.